The Trickle-Down Effects of Supervisor Regulatory Foci on Newcomer Task Performance - Junzhe Zhao; Wenfan Chao; Hang Zhang; Guoxiang Zhao; Minghui Wang (Behavioral Sciences, 2025)
Supervisors’ chronic regulatory foci significantly influence their leadership styles and behaviors, with prevention focus and promotion focus exerting distinct impacts on their actions and outcomes. Drawing on regulatory focus theory, we propose a conceptual model that links supervisor promotion focus and supervisor prevention focus to new employee task performance through the mediating role of supervisor developmental feedback. We conducted a matched questionnaire survey involving 253 supervisor–new employee pairs at two time points. The findings indicated that supervisor promotion focus was positively associated with supervisor developmental feedback, whereas supervisor prevention focus was negatively associated with supervisor developmental feedback. Furthermore, supervisor developmental feedback enhanced new employees’ task performance. This study elucidates the trickle-down effects of supervisor promotion focus and supervisor prevention focus and offers practical implications for organizations on effectively managing supervisors with varying regulatory foci.